Finding Audrey - Kinsella, Sophie (New York : Delacorte Press, 2015)
Fourteen-year-old Audrey is making slow but steady progress dealing with her anxiety disorder when Linus comes into the picture and her recovery gains momentum.
Keywords: Anxiety disorders -- Fiction